'The right flower to stick to': the Unionist Party's questionable choice in 1959. Issue 153 (May 2014) - Smyth, Peter
Abstract : In 1959 the Ulster Unionist Party (U.U.P.) abandoned the idea that relations between the government in Belfast and the two main parties in Westminster should be maintained with a semblance of impartiality. Hitherto, although the Unionist M.P.s at Westminster had taken the Conservative whip, overt criticism of Labour had remained comparatively muted, if only to ensure that those with socialist sympathies would remain under the Unionist umbrella rather than defect to the Northern Ireland Labour Party (N.I.L.P.). In the run-up to the 1959 Westminster general election, however, the U.U.P. not only made offers of unconditional support to the Conservatives, but accompanied them with disparagement of Labour policies and objectives. The logic of that choice was not only contrary to the experience of inter-governmental relations with London since 1945, it also carried a high risk at a time when key areas of the Northern Ireland economy were becoming dependent on support from the British government, and a Conservative victory in the election was by no means certain. It therefore raised the inter-related questions of whether relations with the Labour party had been so toxic, and whether the attitude of the Conservatives, who had been in government in Westminster for most of the decade, had been so benevolent as to justify abandoning the approach which formerly had prevailed. Support for the Conservatives was the U.U.P. default setting, but unless carefully managed, that support carried with it the danger of alienating the Labour party which, given the rotation of power at Westminster, was bound someday to form the government with which Northern Ireland ministers would have to work.